Distal Transradial Access for Recanalization of Chronic Occlusions of the Radial Artery - Salo, Sergii V.; Gavrylyshyn, Andrii Yu.; Levchyshyna, Olena V.; Shpak, Sergii S. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Background. The current state of interventional cardiology is aimed at reducing the number of probable complica-tions of procedures and increasing patient comfort. That is why there was a stage evolution of changing endovascular ap-proaches from transfemoral to transradial. But despite the significant benefits of transradial access, it leaves behind some important complications. One such complication is occlusion of the radial artery. The frequency of this situation ranges from 1 to 30%. That is why the world’s leading interventionists are increasingly using distal transradial access, which is associated with fewer cases of postoperative occlusion of the radial artery. The aim. Occlusion of the radial artery is not an obstacle to changing access to the contralateral artery or more dan-gerous transfemoral access. With distal transradial access it is possible to recanalize artery and provide target procedure. Materials and methods. The study included 318 patients who were scheduled for re-intervention. Among these patients, 12 had a radial artery occlusion, which is 3.7% of the total control group. Successful recanalizations with distal access were performed in 9 patients (75%), and in 3 patients (25%) the attempts were unsuccessful. The technique of recanalization of chronic occlusion included selection of hydrophilic, both non-coronary and coronary wires. At the end of the procedure, hemostasis was performed according to standard procedures using aseptic bandages. Complications of hemostasis were not detected in any patient in the control group. The postoperative period was unremarkable. Conclusions. The study showed the possibility of using distal transradial access to recanalize chronic occlusions of the radial artery, which allows not to waste time on replacement of the contralateral radial artery or life-threatening transfemoral access and perform the necessary amount of the intervention. Besides, this preserves the radial artery for further use in bypass surgery or hemodialysis arteriovenous fistula.